(untitled) (Journal of Environmental Science and Natural Resources, 2013)
A study was carried out to determine the status of heavy metals in farm and urban soils from intensively growing areas of Mymensingh. Sixty three soil samples were collected from 11 upazillas of Mymensingh. From these samples total amount of heavy metals like Pb, Cd, Ni, Cr, Fe and Mn were tested. The soils were also analyzed for texture, pH and organic matter content. The mean concentrations of Pb, Cd, Ni, Cr, Fe and Mn in farm soils were 19.64, 0.32, 39.80, 14.10, 1800.40, 135.66 ?g g-1, respectively and the mean concentrations of above metals in urban soils were 20.93, 0.37, 36.90, 28.85, 1810.08, 127.05 ?g g-1, respectively. The heavy metal concentrations in farm soils were within the limit allowed for maximum acceptable concentration for satisfactory crop production. Heavy metals in urban soils were also below the limit considered as contaminated soil. Most of the heavy metals in both farm and urban soils were negatively correlated with sand and positively correlated with silt. There was no significant correlation between heavy metal content and soil pH or organic matter in both farm and urban soils with very few exceptions. Most of the heavy metals did not show any significant correlation with each other expect Fe which showed significant correlation with Pb, Ni, Cr, Mn and Cd for both farm and urban soils. DOI: http://dx.doi.org/10.3329/jesnr.v5i2.14798 J. Environ. Sci. & Natural Resources, 5(2): 81-84 2012